Aprendizagem da docência sob a perspectiva dos estagiários do curso de Educação Física - Kawamoto, Emilie Erbetta Mahas (2023)
During supervised internships, future teachers can establish their own professional identity, conceived during professional socialization processes and through acquired learning. In inicial training, like the graduation itself, the teaching identity is constituted, especially, with the experiences of the curricular internship with the teacher-collaborators, enabling different types of learning. It is during the supervised curricular internship that future teachers can have contact with the profession, a time when they can learn and build their identities as teachers and contribute to teaching professionalism, which is built throughout a process, with special attention for the work of the collaborating teachers. However, the obligatory internship is complex, since, by involving two institutions, such as the university and the school, articulation is necessary, aiming at joint work in favor of the learning of future teachers. Thus, this research had as its presupposition the following question: What are the learnings identified by the interns of the degree course in Physical Education arising from the Supervised Curricular Internship? It is proposed, as a general objective, to identify and analyze, from the student`s perspective, the learning acquired in the internships. Specifically, we sought to: a) identify and analyze the learning about teaching perceived by Physical Education interns; b) identify and analyze the trainees' perception of the role of the teacher-collaborator in the construction of the teaching identity. The research approach is qualitative, exploratory, using the questionnaire, semi-structured interview and document analysis as data collection techniques. The collected materials were analyzed based on content analysis and, after the analysis, two axes emerged, as follows: “Learnings about teaching in the supervised Curricular Internship”, in which learnings about teaching are perceived and indicated by Physical Education interns during this stage of initial training, as well as the professional profile to be formed and the structure of the internship; and the second, entitled “The role of the teacher-collaborator in the construction of the teaching identity”, in which the perception of the interns about the role that this professional plays in the construction of their identity was identified and analyzed. From the axes presented, we observe that future teachers recognize the importance of internships for graduation, as well as the relevance of the teacher-collaborator in the context of different learning about teaching and the construction of professional identity. We identified that the interns learn elements related to practices linked to the management of class time, the appropriate language for each age group, the use of spaces and the adaptation of materials for Physical Education classes, but they also point out difficulties concerning the relationship between university and school, indicating the need to bring them even closer together. Finally, we found that learning related to teaching can be acquired during internships and, therefore, there is a need for a commitment to teacher training, strengthening the partnership between university and school.